2021
DOI: 10.1016/j.csl.2021.101213
|View full text |Cite
|
Sign up to set email alerts
|

Automatic speaker independent dysarthric speech intelligibility assessment system

Abstract: Dysarthria is a condition which hampers the ability of an individual to control the muscles that play a major role in speech delivery. The loss of fine control over muscles that assist the movement of lips, vocal chords, tongue and diaphragm results in abnormal speech delivery. One can assess the severity level of dysarthria by analyzing the intelligibility of speech spoken by an individual. Continuous intelligibility assessment helps speech language pathologists not only study the impact of medication but als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In Some Cases, Studies Incorporate More Than One Technique. Following That, the Same Study Was Replicated, Thereby Increasing the Overall Number of Research Studies Method/Technique % Reference MFCCs/derived features from MFCCs 35.4% [ 13 , 15 , 55 , 70 , 72 , 80 , 87 , 94 , 95 , 97–99 , 101 , 112 , 117 , 127 , 131 , 133 , 134 ] Spectro-Temporal of utterances/keywords 26.15% [ 12 , 14 , 15 , 26 , 63 , 72 , 87 , 89 , 90 , 97 , 101–103 , 110 , 112 , 124 , 136 ] Articulation way/Speech timing 18.5% [ 13 , 27 , 58 , 81 , 86–88 , 111 , 113 , 124 , 129 ] Glottal flow 7.7% [ 58 , …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Some Cases, Studies Incorporate More Than One Technique. Following That, the Same Study Was Replicated, Thereby Increasing the Overall Number of Research Studies Method/Technique % Reference MFCCs/derived features from MFCCs 35.4% [ 13 , 15 , 55 , 70 , 72 , 80 , 87 , 94 , 95 , 97–99 , 101 , 112 , 117 , 127 , 131 , 133 , 134 ] Spectro-Temporal of utterances/keywords 26.15% [ 12 , 14 , 15 , 26 , 63 , 72 , 87 , 89 , 90 , 97 , 101–103 , 110 , 112 , 124 , 136 ] Articulation way/Speech timing 18.5% [ 13 , 27 , 58 , 81 , 86–88 , 111 , 113 , 124 , 129 ] Glottal flow 7.7% [ 58 , …”
Section: Discussionmentioning
confidence: 99%
“…Combining these two features shows more reliable results than others. [25][26][27] Notably applying ML techniques in speech recognition and augmented communication, enhancing accessibility and user experience, predictive and contextual communication, voice synthesis, and personalized language models. 25,28 ML models can learn and adapt from ML-powered ATS users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mode of meaning included the specific speech inputs into the proposed models. Studies that solely used speech features [15,[24][25][26][27][28][29][30][31][32][33][34][35] were heavily speaker-dependent on their approach and tended to lean more toward intelligibility of the dysarthric speaker than their comprehensibility.…”
Section: Mode Of Meaning Extraction Usedmentioning
confidence: 99%
“…A study has shown that over 47% of dysarthric sufferers reported often repeating what they say as healthy speakers find it difficult to understand them [5]. Speech and Language Pathologists (SLPs) are required to know the severity of dysarthria to assess the progression in the underlying cause of the impairment [6], which helps them to design effective treatment plans, exercises, and recovery sessions, as well as monitor the effectiveness of the therapy [7].…”
Section: Introductionmentioning
confidence: 99%